Pemanfaatan Tepung Silase Usus Ayam sebagai Substitusi Tepung Ikan dalam Formulasi Pakan Benih Patin Siam (Pangasius hypophthalmus) - Tri Sukma (Department of Aquaculture, 2019)
The demand of fish meal as a protein source of feed increases with the increasing of fish culture activities, so this activities needed alternative protein sources to reduce the use of fish meal. The feed ingredient can be used as an alternative protein source is chicken intestine silage meal. The purpose of this research were to determine the percentage of chicken intestine silage meal to substitute fish meal in feed formulation of catfish fry based on the growth and feed efficiency. This research was conducted in June-July 2014 in the Laboratory of Aquaculture, Aquaculture Program, Faculty of Agriculture, Sriwijaya University. Research methods using Completely Randomized Design with six treatments and three replications (A : commercial feed, B: 0% chicken intestine silage meal and 100% fish meal, C: 25% chicken intestine silage meal and 75% fish meal, D: 50% chicken intestine silage meal and 50% fish meal, E: 75% chicken intestine silage meal and 25% fish meal, F: 100% chicken intestine silage meal and 0% fish meal). Results showed the utilization of chicken intestine silage meal significant effect on growth and feed efficiency, but not significant on survival catfish fry. Utilization of chicken intestine silae meal could substitute 100% fish meal in feed formulation of catfish fry. During the study the water quality is still at normal level for the maintenance of catfish fry.